Female Political Representation and Violence against Women: Evidence from Brazil - Magdalena Delaporte; Francisco J. Pino (Institute of Labor Economics (IZA), 2022)
This paper studies the effect of female political representation on violence against women. Using a Regression Discontinuity design for close mayoral elections between female and male candidates in Brazil, we find that electing female mayors leads to a reduction in episodes of gender violence. The effect is particularly strong when focusing on incidents of domestic violence, when the aggressor is the ex-husband/boyfriend, and when victims experienced sexual violence. The evidence suggests that female mayors might implement different policies from male mayors and therefore contribute to reduce gender violence.
Keywords: D72; J16; P16; I18; H75; K42; 330; gender; political economy; elections; violence